Postoperative bile leakage managed successfully by intrahepatic biliary ablation with ethanol - Shimizu, Tetsuya (Baishideng Publishing Group Co., Limited, 2006)
We report a case of postoperative refractory bile leakage managed successfully by intrahepatic biliary ablation with ethanol. A 75-year-old man diagnosed with hepatocellular carcinoma underwent extended posterior segmentectomy including the caudate lobe and a part of the anterior segment. The hepatic tumor attached to the anterior branch of the bile duct was detached carefully and resected. Fluid drained from the liver surface postoperatively contained high concentrations of total bilirubin, at a constant volume of 150 mL per day. On d 32 after surgery, a fistulogram of the drainage tube demonstrated an enhancement of the anterior bile duct. Endoscopic retrograde cholangiography demonstrated complete obstruction of the proximal anterior bile duct and no enhancement of the peripheral anterior bile duct. On d 46 after surgery, a retrograde transhepatic biliary drainage (RTBD) tube was inserted into the anterior bile duct under open surgery. However, a contrast study of RTBD taken 7 mo post-surgery revealed that the fistula remained patent despite prolonged conservative management, so we decided to perform ethanol ablation of the isolated bile duct. Four mL pure ethanol was injected into the isolated anterior bile duct for ten minutes, the procedure being repeated five times a week. Following 23 attempts, the volume of bile juice reached less than 10 mL per day. The RTBD was clamped and removed two days later. After RTBD removal, the patient had no complaints or symptoms. Follow-up magnetic resonance imaging demonstrated atrophy of the ethanol-injected anterior segment without liver abscess formation.